Visible-Light-Induced Singlet Oxygen-Promoted Arylation and Alkylation of Quinoxalin-2(1H)-ones and Quinolines - Renjun Tan; Hequn Yang; Min Jiang; Peijun Song (Molecules)
We report a green and efficient visible-light-driven method for the arylation and alkylation of quinoxalin-2(1H)-ones and quinolines. This catalyst-free process utilizes air as the oxidant, offering mild reaction conditions, environmental sustainability, and broad functional group compatibility. The approach enables the synthesis of aryl and alkyl derivatives of quinoxalin-2(1H)-ones and quinolines with high to excellent yields.